DNA methylation variations of DNA damage response correlate survival and local immune status in melanomas - Min Wang; Xiao‐dong Zhang; Han‐qing Yang; Yang Li; Wen‐mei Chen; An‐an Yin (Immunity, Inflammation and Disease)
Abstract Aim We aimed to explore the impact of DNA methylation alterations on the DNA damage response (DDR) in melanoma prognosis and immunity. Material & methods Different melanoma cohorts with molecular and clinical data were included. Results Hierarchical clustering utilizing different combinations of DDR‐relevant CpGs yielded distinct melanoma subtypes, which were characteristic of different prognoses, transcriptional function profiles of DDR, and immunity and immunotherapy responses but were associated with similar tumor mutation burdens. We then constructed and validated a clinically applicable 4‐CpG risk‐score signature for predicting survival and immunotherapy response. Conclusion Our study describes the close interrelationship among DNA methylation, DDR machinery, local tumor immune status, melanoma prognosis, and immunotherapy response.